Komunikasi Pemasaran Desa Wisata Jabu Sihol Pematangsiantar Melalui Pelestarian Budaya Batak - Saskia Ayu Yolanda (Universitas Muhammadiyah Sumatera Utara, 2022)
There are several components of marketing communication that we can find in the Tourism Village of Jabu Sihol Pematang Siantar such as the communication mix or marketing mix, marketing communication mix, and marketing communication objectives. This strategy is in line with the vision and mission of the Jabu Sihol Tourism Village so that information is conveyed to the target and goes according to what is expected. This study used descriptive qualitative method. The data obtained came from 6 informants. The data sources used in this study were observation, interviews and documentation. written in field notes and then personal documentation, photographic images. The stages in the data analysis process are data reduction, data presentation and conclusions or verification. The results obtained from this study are all subjects feel that the existence of the Jabu Sihol Tourism Village can have an economic impact on the surrounding community. The conclusion of this research is Marketing Communication as a strategy in developing Jabu Sihol Tourism Village Pematang Siantar. And involve the community around the Jabu Sihol Tourism Village in activities to preserve Batak culture.